Role of MRI in assessment of perianal fistula - Mohammed, Haven Azo; Odish, Hayam Yousif (Zanco Journal of Medical Sciences (ZJMS), 2018)
Background and objective: Perianal fistulae commonly occur in middle-aged men. It is important to determine the presence of fistula tracks, its grading and presence of abscess or inflammation. This study aimed to assess the role of MRI in diagnosis and classification of perianal fistula. Methods: This study included 20 patients with perianal sepsis that were referred to the MRI section of Radiology Department in Rizgary Teaching Hospital between August 2015 and April 2016. All patients underwent MRI examination. Results: The mean ± SD age of the 20 patients was 38.5 ± 10.4 years (range 22-55 years), of which 16 patients (80%) were males and four patients (20%) were females. Eighteen patients had a single external opening and two patients had two external opening. All the simple non-branching fistulas were successfully identified by axial and coronal planes of contrast enhanced T1Weighted image fast spin echo, of which five cases had simple intersphincter (G1) fistula and two had simple transphincter (G3), seven cases had intersphincter fistula either secondary tract or horse shoe and abscess (G2), five cases had complex transsphincter (G4). Two cases of complex G4 type had inflammation and edema in ischiorectal and ischioanal fossa and the internal openings were clearer in STIR T2axia. Conclusion: MRI non-invasively offers important information about perianal fistula that can reduce surgical complications and postoperative recurrence of the disease. Every patient with suspicious perianal sepsis should undergo MRI examination to prevent complications and morbidity.